Kontribusi dan Motivasi Keluarga Korban Bencana Sigi dalam Beternak Ayam KUB Bantuan BALITBANGTAN - Mardiana Dewi; Masyitah Muharni; Wardi Wardi; Heni Sulistyawati Purwaning Rahayu (Politeknik Negeri Jember, 2020)
The natural disasters of the earthquake, liquefaction, and tsunami that occurred on September 28,2018 in Palu, Sigi, and Donggala have caused damage and even loss of residence and property ofthe people in the region. Agricultural land which was a source of livelihood could not be reused.During the recovery phase in the aftermath of natural disasters, the government andhumanitarian agencies could rebuild facilities and infrastructure including the economy ofdisaster victims. Central Sulawesi Assessment Institute for Agricultural Technology (AIAT)participated in the socio-economic recovery of natural disaster victims in Sigi Regency through thedevelopment of superior BALITBANGTAN (KUB) chicken based on native households in temporaryshelters in Jono Oge Village, Sigi Regency. The purpose of this study was to determine thecontribution and motivation of Sigi disaster victims in raising KUB chickens based on households.The contribution of raising KUB chicken was calculated from the percentage of KUB chicken tototal household income while motivation was measured by the scoring method using a Likert scale.Based on the results of the assessment, it was concluded that the income of victims of naturaldisasters at the Jono Oge Village in Sigi Regency had contribution contribution of raising KUBchickens based on households was 8.08% categorized at <Rp1,500,000.00 and 4.21% categorize atRp1,500,000.00 - Rp2,500,000.00. The motivation of natural disaster victims for raising KUBchickens was on the ease of sales and maintenance.